Kehadiran Saksi Ahli dalam Penyelesaian Perkara Keluarga di Pengadilan Agama di Indonesia - Safitri, Melani Intan (Universitas Pahlawan Tuanku Tambusai, 2024)
In the process of carrying out a marriage, of course, there are many preparations that must be made. This marriage readiness also has various criteria. Each individual, both men and women, has their own perspective on readiness due to many influencing factors. From a socio-cultural point of view, women tend to be seen as inferior to men, where the status of head of the family is assigned to men. In addition, there are differences in the responsibilities of a husband and wife. This is one of the underlying differences in the priority of marriage readiness of young men and women. This research is a qualitative study with field research methods through interviews. After conducting interviews with informants, it was found that gender does not determine a person's readiness to get married. In general, men and women have the same views regarding the readiness that must be done before marriage but differ in priority positions. Male informants tend to put economic readiness in the first place because of a sense of responsibility to provide for their families in the future. Meanwhile, female informants prioritize spiritual knowledge and emotional readiness.